2018
DOI: 10.1186/s13065-018-0507-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, molecular docking, analgesic, antiplatelet and anticoagulant effects of dibenzylidene ketone derivatives

Abstract: In this study dibenzylidene ketone derivatives (2E,5E)-2-(4-methoxybenzylidene)-5-(4-nitrobenzylidene) cyclopentanone (AK-1a) and (1E,4E)-4-(4-nitrobenzylidene)-1-(4-nitrophenyl) oct-1-en-3-one (AK-2a) were newly synthesized, inspired from curcuminoids natural origin. Novel scheme was used for synthesis of AK-1a and AK-2a. The synthesized compounds were characterized by spectroscopic techniques. AK-1a and AK-2a showed high computational affinities (E-value > − 9.0 kcal/mol) against cyclooxygenase-1, cyclooxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Cyclopentanone derivatives have been reported to exhibit anti-inflammatory, analgesic, antioxidant, anticoagulant, anti- AChE , and anti- BChE activities [ 8 , 9 , 10 , 11 ]. Following up on this perspective the cyclopentanone derivative 2-(hydroxy-(3-nitrophenyl)methyl)cyclopentanone (3NCP, Figure 1 ) [ 12 ] was evaluated as a possible potential candidate against AD.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopentanone derivatives have been reported to exhibit anti-inflammatory, analgesic, antioxidant, anticoagulant, anti- AChE , and anti- BChE activities [ 8 , 9 , 10 , 11 ]. Following up on this perspective the cyclopentanone derivative 2-(hydroxy-(3-nitrophenyl)methyl)cyclopentanone (3NCP, Figure 1 ) [ 12 ] was evaluated as a possible potential candidate against AD.…”
Section: Introductionmentioning
confidence: 99%
“…The current study reported the isolation of four compounds from W. coccinea including 3β-acetyloxy-olean-12-en-28-ol, wrightiadione, 22β-hydroxylupeol, and β-sitosterol [45][46][47][48]. According to the best of our knowledge, this is the first investigation on W. coccinea to report these bioactive phytoconstituents.…”
Section: Discussionmentioning
confidence: 99%
“…Computational docking was conducted to reveal the potential bioactivities of the identified compounds including antioxidant, cytotoxicity, antidiarrheal, hypoglycemic, and analgesic properties. To run the molecular interaction and determine the radical scavenging capacity, cytotoxicity, antidiarrheal, hypoglycemic, and central and peripheral analgesic properties, glutathione reductase (PDB ID: 3GRS), epidermal growth factor receptor (PDB ID: 1XKK), kappa opioid receptor (PDB ID: 6VI4), glucose transporter 3 [GLUT 3] (PDB ID: 4ZWB), Mu-opioid receptor (PDB ID: 5C1M), and cyclooxygenase 2 (COX-2) (PDB ID: 1CX2) proteins were selected based on the biochemical mechanisms and the current evidence [36,[42][43][44][45][46]. The targeted proteins' three-dimensional (3D) crystal structures were retrieved from the RCSB protein data bank (https://www.rcsb.org; accessed on 1 January 2022) and were saved in PDB format.…”
Section: Target Protein Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, at the same concentration, 103 and 72 increase the plasma recalcification time compared to the saline group) respectively. Finally, treatment with 103 and 72 at doses of 100, 300, or 1000 μg/kg prolong the bleeding time [43].…”
Section: Antiparasitic Activitymentioning
confidence: 95%